2012
DOI: 10.1182/blood-2012-02-409813
|View full text |Cite
|
Sign up to set email alerts
|

Detectable minimal residual disease before hematopoietic cell transplantation is prognostic but does not preclude cure for children with very-high-risk leukemia

Abstract: In patients with acute leukemia, detection of minimal residual disease (MRD) before allogeneic hematopoietic cell transplantation (HCT) correlates with risk of relapse. However, the level of MRD that is most likely to preclude cure by HCT is unclear, and the benefit of further chemotherapy to reduce MRD before HCT is unknown. In 122 children with very-high-risk acute lymphoblastic leukemia (ALL; n = 64) or acute myeloid leukemia (AML, n = 58), higher MRD levels at the time of HCT predicted a poorer survival af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 33 publications
(45 reference statements)
9
140
1
1
Order By: Relevance
“…For those at a higher risk, MAC HCT might be considered to improve the leukemic control. 2,51,52 In patients who do not meet strict CR criteria and so are unfit to undergo a MAC allo-HCT, experimental targeted therapies and/or cellular therapies (for example, tyrosine kinase inhibitors in FLT-3-positive patients, hypomethylating agents 53 or haploidentical natural killer cell therapy 54 ) might be preferred over further conventional drug consolidation as a bridging therapy to allo-HCT. Consolidation chemotherapies did not improve allo-HCT outcome before either MAC or RIC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…For those at a higher risk, MAC HCT might be considered to improve the leukemic control. 2,51,52 In patients who do not meet strict CR criteria and so are unfit to undergo a MAC allo-HCT, experimental targeted therapies and/or cellular therapies (for example, tyrosine kinase inhibitors in FLT-3-positive patients, hypomethylating agents 53 or haploidentical natural killer cell therapy 54 ) might be preferred over further conventional drug consolidation as a bridging therapy to allo-HCT. Consolidation chemotherapies did not improve allo-HCT outcome before either MAC or RIC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Employing this assumption, as opposed to using the data reported in Leung et al 111 for this population, provided a more consistent prediction of survival data from Lee et al, 164 in which it was reported that all 10 HSCT recipients with a MRD-negative status were leukaemia free and alive at the end of study follow-up.…”
Section: Efficacy Parameter Estimatesmentioning
confidence: 88%
“…110,111,189 These studies have shown, to varying degrees, that MRD status prior to HSCT appears to be an important prognostic determinant of long-term RFS and OS, with MRD-negative (< 0.01% marrow blasts) patients experiencing superior survival compared with MRD-positive (> 0.01% to 5% marrow blasts) patients, including within studies of children with relapsed ALL. These data support the assumption of a continuous relationship between MRD level prior to HSCT and 5-year survival probability.…”
Section: Input Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walter et al have reported that MPFC detectable MRD prior to HCT is independently associated with relapse after HCT [17]. Since MRD prior to HCT reflects ineffectiveness of chemotherapy prior to HCT these results suggest that ineffective chemotherapy begets ineffective HCT, although the effect pre HCT of a given increment in MPFC detectable MRD seems greater, at least in children, in ALL than in AML [18].…”
Section: Minimal Residual Disease (Mrd)mentioning
confidence: 99%